Rapid detection and identification of human hookworm infections through high resolution melting (HRM) analysis - Ngui, Romano; Lim, Yvonne Ai Lian; Chua, Kek Heng (Public Library of Science, 2012)
BACKGROUND Hookworm infections are still endemic in low and middle income tropical countries with greater impact on the socioeconomic and public health of the bottom billion of the world's poorest people. In this study, a real-time polymerase chain reaction (PCR) coupled with high resolution melting-curve (HRM) analysis was evaluated for an accurate, rapid and sensitive tool for species identification focusing on the five human hookworm species. METHODS Real-time PCR coupled with HRM analysis targeting the second internal transcribed spacer (ITS-2) of nuclear ribosomal DNA as the genetic marker was used to identify and distinguish hookworm species in human samples. Unique and distinct characteristics of HRM patterns were produced for each of the five hookworm species. The melting curves were characterized by peaks of 79.24±0.05°C and 83.00±0.04°C for Necator americanus, 79.12±0.10°C for Ancylostoma duodenale, 79.40±0.10°C for Ancylostoma ceylanicum, 79.63±0.05°C for Ancylostoma caninum and 79.70±0.14°C for Ancylostoma braziliense. An evaluation of the method's sensitivity and specificity revealed that this assay was able to detect as low as 0.01 ng/µl hookworm DNA and amplification was only recorded for hookworm positive samples. CONCLUSION The HRM assay developed in this study is a rapid and straightforward method for the diagnosis, identification and discrimination of five human hookworms. This assay is simple compared to other probe-based genotyping methods as it does not require multiplexing, DNA sequencing or post-PCR processing. Therefore, this method offers a new alternative for rapid detection of human hookworm species.